PERAN SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN EFEKTIFITAS PERUSAHAAN: Peran Sistem Informasi Manajemen dalam Meningkatkan Efektivitas Perusahaan - Mhd Yudha Sirgi Ardhana; Rayyan Firdaus (PT. Intelek Cendikiawan Nusantara, 2024)
This research analyzes the implementation of a company's marketing strategy by focusing on four main aspects: price, product, distribution and promotion. The research method involves comprehensive data analysis from 20 respondents, consisting of management, operational employees and company customers. Research findings show that the company has implemented a competitive pricing strategy, but high price fluctuations are a potential problem that affects customer satisfaction. The company's product strategy has included product diversification and development, although there have been complaints regarding limited product choices for some market segments. On the distribution side, a multi-channel strategy has been implemented, but delivery delays in online transactions indicate the need for improvements in supply chain management. Apart from that, company promotions have varied but need to increase the intensity and synergy between offline and online promotions to achieve maximum effectiveness. In conclusion, although the company's marketing strategy has reflected a comprehensive effort to increase competitiveness and customer satisfaction, there are still several aspects that require further attention to achieve optimal results in an increasingly competitive market environment.